OPTIMIZATION OF LIGHTNING PROTECTION SYSTEM DESIGN FOR MULTI-STORY BUILDINGS BASED ON COST AND PROTECTION COVERAGE ANALYSIS - Ahmad Nasrul (Khamdan Karya Cipta, 2026)
The installation of a lightning protection system at SMK Bhakti Praja Jepara aims to safeguard the building from the hazards of lightning strikes. The building, which is 23 meters high with an area of ±3,716 m², currently lacks this protective system, making it susceptible to mechanical, thermal, and electrical damage. This study began by planning a lightning protection system in accordance with the PUIPP (General Regulations for Lightning Protection Installation) and SNI 03-7015-2004 standards. The research process involved collecting building data, measuring grounding resistance, and conducting a comparative analysis between two methods: conventional and electrostatic. The grounding resistance measurements yielded values of 3.88 Ohm, 1.39 Ohm, and 3.77 Ohm, all of which meet the SNI standards. The comparative analysis concluded that the conventional system, which requires four lightning rods, has an estimated cost of Rp 7,537,774.00. In contrast, the electrostatic system, due to its wider protection radius, only requires one lightning rod and is more cost-efficient, with an estimated budget of Rp 5,723,774.00. Based on these findings, it is concluded that the electrostatic lightning protection system is a more optimal solution in terms of both protection radius effectiveness and cost efficiency.